Transculturalism Instead of National Mythologies? Historical Research of Cultural Exchange Processes - Čapská, Veronika; Storchová , Lucie (Dějiny – teorie – kritika, 2015)
The study introduces a bloc of articles which explore the growing field of the so called relational approaches to history. It present a critical overview of the developments of the theoretical and methodological discussions in the last thirty years. The authors understand the label “relational history” as an umbrella term for a broad spectrum of approaches which analyse transfers, interactions, interconnectedness and interdependencies of historical phenomena and share the ambition to overcome the national interpretational frameworks. The article shows that the methodological debates often continue to be marked by national contexts (one can mention for example the French-German debate on cultural transfer and histoire croisee or the Anglophone preference for the so called concept of transnationalism which itself refers to an idea of a nation). The authors see opportunities for a reflective research and more refined analytical approaches particularly in a systematic border-crossing and intensive collaboration of relational history with other disciplines.